(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
The proposed paper presents the topic “Deployment of Docker Services on Private Cloud”. It briefs how the system is implemented to provide Docker services to client, in order to reduce client’s overall system load and to make the client enjoy the application layer facilities easily. The paper tells how this system uses Docker Hub which works on the concept of Container as a Service, thus making the task of creating, deploying and running applications simpler and light weighted. Docker Server in this system acts as a bridge between Docker client and Docker Hub. Client requests server for applications, server fetches the images from Docker Hub via Docker Engine which is responsible for packing these images along with its dependencies and binaries into a Container. Client can access these applications using web browser (URL,Tags). Traditionally, server could access Docker through Command Line Interface (CLI); hence to make it simpler, we present this paper illustrating creation of User Interface (UI) for the server side. Thus this paper summarizes how Docker services are deployed on private cloud